Novel Frameworks for Lightweight & Robust Cache Contention Analysis - Gomes, Cesar. (Tufts University. Tisch Library., 2023)
Thesis (Ph.D.)--Tufts University, 2023.; Submitted to the Dept. of Electrical Engineering.; Advisor: Mark Hempstead.; Committee: Hwa Chang, Soha Hassoun, and Aamer Jaleel.; Keyword: Computer engineering.